Preliminary investigations of the endoparasite component communities of stray cats from Kuala Lumpur - Syed-Khalil, S.A.A.; Mohd Zain, S.N. (2007)
Investigations into the endoparasite fauna of stray cats from Kuala Lumpur were carried out to determine the present population and diversity. Post-mortem examinations of selected organ from 85 cats revealed that 87.1% cats harbored endoparasites, with an average of 36.65 worms per infected cat. Endoparasite recovered consists of five nematode species (Toxocara catti, Toxocara malayensis, Ancylostoma ceylanicum, Ancylostoma braziiiensie and Strongyloides sp.), two cestode species (Dipylidium caninum and Taenia taeniaformis) and one trematode species (Platynosomum fastosum). Toxocara sp. was shown to have the highest prevalence and mean intensity values. Present observations provided additional insights to the environment, behavior and diet of the local strays. Ancylostoma ceylanicum, Ancylostoma broziliensie, Toxocara catti and Dipylidium caninum are known to be of medical significance.